Pengaruh Fasilitas dan Pelayanan terhadap Loyalitas Pelanggan pada Cafe Tepian Laut Merak - Monica Septiani; Suhroji Adha; Hero Wirasmara Kusuma (Epsilon Journal of Management, 2025)
This study aims to analyze the influence of facilities and service quality on customer loyalty at Café Tepian Laut Merak. The research employed a quantitative approach with a total sample of 100 respondents selected using a purposive sampling technique. Data were collected through questionnaires distributed to customers who had visited the café. The data analysis was conducted using SPSS version 22, which included validity testing, reliability testing, classical assumption testing, partial linear regression analysis, and multiple linear regression analysis. The results showed that the facility variable (X1) had a positive and significant effect on customer loyalty (Y), indicating that better facilities contribute to higher customer loyalty. Likewise, the service variable (X2) also had a positive and significant effect on customer loyalty, suggesting that high-quality service enhances customer satisfaction and loyalty. Simultaneously, both facilities and service quality significantly influence customer loyalty at Café Tepian Laut Merak. These findings highlight the importance of improving both physical facilities and service quality as key strategies to maintain and increase customer loyalty in the competitive culinary business sector.